1989
DOI: 10.1002/anr.1780320224
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic fever and poststreptococcal glomerulonephritis: A case report

Abstract: LETTERSthe IgG galactose deficiency seen in rheumatoid arthritis and in a relatively small number of patients with systemic lupus erythematosus (SLE) and Crohn's disease as evidence that changes in carbohydrate are merely a consequence of chronic inflammation.We have set out at some length (2) the arguments for the view that structural changes involving galactose in the Fcy oligosaccharides are restricted to certain diseases. In particular, we have determined the percentage of IgG oligosaccharide chains lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…Among these previously reported cases, two were adults [1] and six patients presented with the combination of an initial episode of ARF with carditis along with APSGN [4,7,10,11,12,13], which is similar to the present case; another three reported cases developed APSGN during a recurrent episode of ARF [1,6,8]. The case presented by Kakkera et al [7] had pancarditis with pericardial effusion and this unique feature was also found in our case.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Among these previously reported cases, two were adults [1] and six patients presented with the combination of an initial episode of ARF with carditis along with APSGN [4,7,10,11,12,13], which is similar to the present case; another three reported cases developed APSGN during a recurrent episode of ARF [1,6,8]. The case presented by Kakkera et al [7] had pancarditis with pericardial effusion and this unique feature was also found in our case.…”
Section: Discussionsupporting
confidence: 85%
“…Imanaka et al [6] presented one case with APSGN and ARF appearing at the same time, which is similar to our case. Erythema marginatum happened in only 1 of the 12 reported cases [8]. The picture of erythema marginatum in our patient was unlike the case reported by Kujala et al [8], who presented with a larger central clear region, while the short duration and evanescent characteristics were similar between the two cases.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Although both ARF and APSGN develop following GAS infection, the two diseases have different epidemiology, immunology and bacteriology, and simultaneous occurrence of them in the same patient is rare (Lin et al, 2007). Since Gibney et al first reported a patient with co-occurrence of ARF and histologically proven APSGN (Gibney et al, 1981), seventeen patients with concurrent ARF and APSGN have been reported (Akasheh et al, 1995;Ben-Dov et al, 1985;Castillejos et al, 1985;Imanaka et al, 1995;Kakkera et al, 1998;Kujala et al, 1989;Kula et al, 2003;Kwong et al, 1987;Lin et al, 2003;Mastell et al, 1990;Öner, et al, 1993;Said et al, 1986;Sieck et al, 1992;Sinha et al, 2007).…”
Section: Acute Rheumatic Fevermentioning
confidence: 99%